2020
DOI: 10.1186/s10195-020-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and reproducibility of the new AO/OTA 2018 classification system for proximal humeral fractures: a comparison of three different classification systems

Abstract: Background: The classification systems for proximal humeral fractures routinely used in clinical practice include the Neer and Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association (AO/OTA) 2007 systems. Currently used systems have low inter-and intraobserver reliability. In 2018, AO/OTA introduced a new classification system with the aim of simplifying the coding process, in which the Neer four-part classification was integrated into the fracture description. The aim of the present work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…When assessing the reliability and reproducibility of the AO/OTA 2018 classification compared with the previous AO/OTA 2007 and Neers classification for proximal humeral fractures a substantial mean inter- and intra-rater agreement was seen for the AO/OTA 2018 system. The interrater agreement was substantially higher for the AO/OTA 2018 compared with the AO/OTA 2007 classification ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…When assessing the reliability and reproducibility of the AO/OTA 2018 classification compared with the previous AO/OTA 2007 and Neers classification for proximal humeral fractures a substantial mean inter- and intra-rater agreement was seen for the AO/OTA 2018 system. The interrater agreement was substantially higher for the AO/OTA 2018 compared with the AO/OTA 2007 classification ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…The interobserver reliability of the general AO and full Neer classification systems has been studied intensively. However, many of these studies had a limited number of observers, which could result in overestimation of agreement, and the question remained unanswered as to the interobserver agreement for the subgroups of surgical neck fractures (Neer included three subgroups, and AO included two subgroups) [ 14 , 15 ]. Regarding the AO classification, the largest study included 46 observers and found a kappa of 0.18 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of Current Procedural Terminology (CPT) codes, trauma registries, and operative logs between 2005 and 2015 was conducted at 5 trauma centers to identify patients who sustained isolated low-energy proximal humerus fractures (OTA/AO 11 A-C) initially treated nonoperatively. 16,17 To be included, patients needed to be skeletally mature and have an isolated low-energy proximal humerus fracture. Skeletally immature individuals, patients with pathologic fractures, patients who were nonambulatory before their injury, and those unable to follow-up at least 84 days were excluded from review and analysis.…”
Section: Methodsmentioning
confidence: 99%